BLOOD PLASMA PROTEIN PRODUCTION AND UTILIZATION : THE INFLUENCE OF AMINO ACIDS AND OF STERILE ABSCESSES - Madden, S. C. (The Rockefeller University Press, 1940)
When blood plasma proteins are depleted by bleeding with return of the washed red blood cells (plasmapheresis) it is possible to bring dogs to a steady state of hypoproteinemia and a uniform plasma protein production on a basal low protein diet. These dogs are clinically normal. Introduction of variables into their standardized life gives insight into the production of plasma protein. Casein retested as the basal protein in the ration may show high yield of plasma protein, equal to 33 per cent of the protein fed. This equals the potency of liver protein (17 to 33 per cent) and approaches the utilization of plasma protein by mouth (40 per cent). Zein has no effect upon plasma protein regeneration but when it is supplemented with cystine, tryptophane, lysine, and glycine, there is a doubling of the liver basal plasma protein production and a retention of the fed protein nitrogen. Threonine does not modify the above reaction. Liver protein supplemented with cystine, leucine, glutamic acid, and glycine in the basal diet yields double the amount of new formed plasma protein compared with liver alone. This combination is then as potent as plasma protein itself when given by mouth—40 per cent utilization. Tyrosine or lysine, arginine, and isoleucine do not modify the above responses. Methionine is not as effective as cystine in supplementing gelatin and tyrosine to produce plasma protein. Cystine, leucine, and glutamic acid appear to be of primary importance in the building of new plasma protein in these experiments. Plasma protein formation is dependent upon materials coming from the body reserve and from the diet. Given an exhaustion of the reserve store there is very little plasma protein produced during a protein fast (3 to 6 gm. per week). A turpentine abscess does not modify this fasting plasma protein reaction. Homologous plasma given by vein will promptly correct experimental hypoproteinemia due to bleeding. It will maintain nitrogen equilibrium and replenish protein stores. Even during hypoproteinemia plasma protein may promptly pass out of the circulation to supply body needs for protein. Perhaps the most significant concept which derives from all these experiments is the fluidity of the body protein (including plasma protein)—a ready give and take between the protein depots—a "dynamic equilibrium" of body protein.